A Study of Safety and Effectiveness of Evicel Fibrin Sealant as an Adjunctive Hemostat in Pediatric Surgery - Kenny, Simon; Gabra, Hany; Hall, Nigel J.; Flageole, Helene; Illie, Bogdan; Barnett, Ellie; Kocharian, Richard; Sharif, Khalid (European Journal of Pediatric Surgery, 2024)
Introduction Data on the use of fibrin sealants to control intraoperative bleeding in children are scarce. Evicel Fibrin Sealant (Ethicon Inc., Raritan, New Jersey, United States) was found safe and effective in clinical trials of adults undergoing various surgery types. We evaluated the safety and efficacy of Evicel versus Surgicel Absorbable Hemostat (Ethicon Inc.) as adjunctive topical hemostats for mild/moderate raw-surface bleeding in pediatric surgery.Methods A phase III randomized clinical trial was designed as required by the European Medicines Agency's Evicel Pediatric Investigation Plan: 40 pediatric subjects undergoing abdominal, retroperitoneal, pelvic, or thoracic surgery were randomized to Evicel or Surgicel, to treat intraoperative mild-to-moderate bleeding. Descriptive analyses included time-to-hemostasis and rates of treatment success (4, 7, 10 minutes), intraoperative treatment failure, rebleeding, and thromboembolic events.Results Forty of 130 screened subjects aged 0.9 to 17 years were randomized 1:1 to Evicel or Surgicel. Surgeries were predominantly open abdominal procedures. The median bleeding area was 4.0 cm2 for Evicel and 1.0 cm2 for Surgicel. The median time-to-hemostasis was 4.0 minutes for both groups. The 4-, 7-, and 10-minute treatment success rates were 80.0% versus 65.0%, 100.0% versus 80.0%, and 95.0% versus 90.0%, whereas treatment failure rates were 5.0% versus 25.0%, for Evicel and Surgicel, respectively. No deaths or thrombotic events occurred. Re-bleeding occurred in 5.0% of Evicel and 10.0% of Surgicel subjects.Conclusions In accordance with adult clinical trials, this randomized study supports the safety and efficacy of Evicel for controlling mild-to-moderate surgical bleeding in a broad range of pediatric surgical procedures.
Keywords: pediatric surgery; bleeding; hemostasis; topical hemostat; fibrin sealant